Photobiomodulation therapy to treat neuropathic oral pain after contagion by COVID-19: Laser treatment of Neuropathic Pain after COVID-19 - Gomes, Fernanda Cruz; Naurath, Christian; Hiramatsu Azevedo, Luciane; Zezell, Denise Maria (Brazilian Dental Science, 2021)
Objective: The purpose of this short communication is to show that although photobiomodulation in the treatment of neurophathic oral pain after COVID-19 contagion could be an option, photobiomodulation is not a new technique. PBMT was used with different protocols and pain was assessed using VAS (visual analogue scale - 0 until 10) before and after the consultation. Results: Evolution of VAS during the sessions showed a decrease in painful symptomatology as treatment was performed. Conclusion: Based on the results obtained in the present case report, we concluded that PBMT with the parameters used in this clinical case was an effective, noninvasive and a new option of treatment for neuralgia resulting from COVID-19. KEYWORDS Laser; Photobiomodulation therapy; COVID-19; Oral neuralgia.